DAMPAK RETRIBUSI SEBAGAI PENDAPATAN ASLI DESA TERHADAP KEMANDIRIAN KEUANGAN DESA (Studi Desa Kuntu Kecamatan Kampar Kiri Kabupaten Kampar) - Selamat, Gus Endrawan (LP2M Universitas Muslim Nusantara Al Washliyah, 2023)
This research is a qualitative study using a descriptive method. The informants in the study were determined through purposive sampling. The types of data in this research consist of primary and secondary data, collected through documentation study as the data collection technique. The data analysis was conducted through several stages, including data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that retribution does not have an impact on the financial independence of the village. However, the services provided to the community generate satisfaction among the residents. The purpose of this research is to describe the impact of retribution as the village's own revenue on the financial independence of Kuntu Village.